A Case Study of Utilization of Abortion Service in the Tertiary Hospital of Western Region of Nepal - Chaudhary, Rajendra Kumar; Jha, Nirmal Kumar; Manandhar, Bijay; Chaudhary, Krishna (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Unsafe abortion is one of the major public health problems in developing countries including Nepal. After integration of comprehensive abortion care in safe motherhood service, there has been improvement in maternal and women health in Nepal. Furthermore, improvements are required in raising awareness and accessibility to safe abortion services to all the women in throughout the country. Methods: This is a retrospective study carried out in Western Regional Hospital after reviewing the data from the hospital records. Demographic details, parity, types of abortion for spontaneous abortion, and methods of induced abortion were noted and analyzed. Results: Maximum number of women belonged to 20-24 years of age and is Brahmin/Chhetri. Multi gravida are more than primi and they underwent induced abortion by medical termination of pregnancy. Similarly, incomplete abortion was in highest number among the spontaneous abortion. Conclusion: Easy availability of the safe abortion services and awareness among the people regarding it would certainly improve the maternal health and quality of life.